Galileo's pendulum : from the rhythm of time to the making of matter - Newton, Roger G. (Cambridge, Mass. ; London : Harvard University Press, 2005)
Bored at Mass at the cathedral in Pisa, the seventeen-year-old Galileo regarded the chandelier swinging overhead and remarked to his great surprise, that the lamp took as many beats to complete an arc when hardly moving as when it was swinging widely. Galileo's Pendulum tells the story of what this observation meant, and of its profound consequences for science and technology.
Biological timekeeping : the body's rhythms -- Calendar : different drummers -- Early clocks : home-made beats -- The pendulum clock : the beat of nature -- Successors : ubiquitous timekeeping -- Isaac Newton : the physics of the pendulum -- Sound and light : oscillations everywhere -- Quantum : oscillators make particles.
Originally published: 2004.
Includes bibliographical references and index.
Keywords: Time measurements; Pendulum